2023
DOI: 10.3390/pr12010053
|View full text |Cite
|
Sign up to set email alerts
|

From Segmentation to Classification: A Deep Learning Scheme for Sintered Surface Images Processing

Yi Yang,
Tengtuo Chen,
Liang Zhao

Abstract: Effectively managing the quality of iron ore is critical to iron and steel metallurgy. Although quality inspection is crucial, the perspective of sintered surface identification remains largely unexplored. To bridge this gap, we propose a deep learning scheme for mining the necessary information in sintered images processing to replace manual labor and realize intelligent inspection, consisting of segmentation and classification. Specifically, we first employ a DeepLabv3+ semantic segmentation algorithm to ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Deep learning is regarded as an excellent tool for simulating the structure and thinking of the human brain. To effectively manage the quality of iron ore, a deep learning scheme for mining the necessary information in sintered image processing [40] was proposed to replace manual labor and realize intelligent inspection. Experiments showed that the improved semantic segmentation model can effectively segment the sintered surface, achieving 98.01% segmentation accuracy with only a 5.71 MB size.…”
Section: Data-driven Optimization and Deep Leaning Methodsmentioning
confidence: 99%
“…Deep learning is regarded as an excellent tool for simulating the structure and thinking of the human brain. To effectively manage the quality of iron ore, a deep learning scheme for mining the necessary information in sintered image processing [40] was proposed to replace manual labor and realize intelligent inspection. Experiments showed that the improved semantic segmentation model can effectively segment the sintered surface, achieving 98.01% segmentation accuracy with only a 5.71 MB size.…”
Section: Data-driven Optimization and Deep Leaning Methodsmentioning
confidence: 99%